Hungarian Monitoring, 14 July 1988 . [Magyar rádiófigyelő], 1988. július 14 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Gorbachev takes part in Warsaw Pact body meeting - Situation in Yerevan - Situation in Karabakh Domestic Affairs: - Károly Grósz travels to Warsaw Pact meeting in Warsaw - Hungarian Socialist Workers' Party (MSZMP) Central Committee in session - Rezső Bányász's information on the government meeting Economy: - Foreign Trade Bank in communication with VISA International - Entrepreneurial taxes to be introduced next year Külpolitika: - Gorbacsov részt vesz a VSZ testületi ülésén - Jereváni helyzet - Karabahi helyzetkép Belpolitika: - Grósz Károly a VSZ ülésére utazik Varsóba - MSZMP KB ülés - Bányász Rezső tájékoztatója a kormányülésről Gazdaság: - A Külkereskedelmi Bank felveszi a kapcsolatot a VISA International-el - Jövőre bevezetik a vállalkozói adók